Structural Controls on Cu Metallogenesis in the Dehaj Area, Kerman Porphyry Copper Belt, Iran: A Remote Sensing Perspective - G. Mirzababaei; J. Shahabpour; A. Zarasvandi; S. M. Hayatolgheyb (Journal of Sciences, Islamic Republic of Iran)
Structural analysis of remotely sensed data provides a method of assessing the structural significance of regional metallogenesis in the Dehaj area as the northwestern part of the Kerman porphyry Cu belt. This belt is consisted of dominant Eocene volcanics and the Dehaj type subvolcanic intrusives. In the study area, geologically, Cu-mineralization is hosted by the Kuh-e-Panj type subvolcanic intrusives. Photogeological analysis of the Landsat imagery reveals a pattern of mainly NW-SE oriented linear structures which were apparently generated in response to crustal thickening and lineament reactivations during the generation of a huge stratovolcanoes. A comparison of lineament map generated from Landsat ETM+ image indicates that the locations of some of the deposits, magmatic and hydrothermal centers are at/or close to the intersections of linear structures. This study deals also with the irrefutable genetic links between some small circular features and copper mineralization that has not been previously examined. It is proposed that the circular features are superficial expressions of intruded stocks or bodies in subvolcanic levels without remarkable volcanic equivalents. Of particular matter in this framework is the possible genetic/age relationship between the linear structures and the circular features. These small circular features are thought, in some cases, as having been formed due to development of the local extensional points near the intersection of the linear structures in a regional, tectonically, compressive environment. Regionally, plotting the residual anomaly and bouguer anomaly maps of the region provides, geophysically, a lucid explanation as to how the small circles came into existence.